STUDI FENOMENOLOGI IBU THALLER DI RUMAH SAKIT UMUM DAERAH KARAWANG - Siti Nursanti; Vinny Putri Frissilya; Yanti Tayo; Wahyu Utamidewi (Universitas Lambung Mangkurat, 2020)
Thalassemia is a blood disorder or acute anemia that cannot be cured. The role of a mother in caring for a child is the most important role, especially for a mother of a term Thaller used for thalassemia patients. In caring for a Thaller the mother will have its meaning about Thalassemia and has a business looking for treatment with certain reasons to keep her child healthy. This study relates to how the mother interpreted Thalassemia and how the mother's communication experience in carrying out her profession as a mother Thaller. The researcher used a qualitative method with a phenomenological approach to a study that wanted to gain knowledge about a mother Thaller in interpreting her profession from the results of her conscious experience. The theory used in this study is the Phenomenology theory Alferd Schutz and the Symbolic Interaction theory. With 3 informants. The results of the research on the meaning of Thalassemia according to the informants' point of view are that Thalassemia is not an obstacle in getting along and facing the general public and is not a differentiator that makes their children different from other children and makes Thalassemia a test of life that must be faced in any form. Their motive for continuing treatment for their children is that they want their children to be healthy and heal, even though in reality they cannot be cured and must continue to undergo treatment without any complaints.